DISSOCIATION BETWEEN LONG-TERM WEIGHT LOSS INTERVENTION AND BLOOD PRESSURE. AN 18-MONTH RANDOMIZED CONTROLLED TRIAL. (April 2021) - Gepner, Yftach; Goldstein, Nir; Shelef, Ilan; Schwarzfuchs, Dan; Zelicha, Hila; Meir, Anat Yaskolka; Tsaban, Gal; Grossman, Ehud
Abstract : Objective: Obesity is associated with elevated blood pressure (BP). In patients with obesity and hypertension, weight loss lowers BP, but the long-term effect of weight loss on BP is less clear. We aimed to assess the effect of long-term weight loss intervention on BP in normotensive and hypertensive subjects. Design and method: In an 18-month trial, 278 subjects (mean age 47.9 ± 9.3 years, 89% male, 56% hypertensive) with abdominal obesity or elevated serum triglycerides and low high-density-lipoprotein cholesterol were recruited for weight loss intervention. Body weight and BP were measured at baseline, after 6 and 18 months. Results: After 6 months of intervention, in the weight loss phase, body mass index (BMI) decreased by an average of -2.2 ± 1.5 kg/m2 (p < 0.001) and both diastolic BP (DBP) and systolic BP (SBP) decreased by -2.1 ± 8.8 mmHg, and -2.3 ± 12.9 mmHg, respectively (P < 0.01 for both). The change in BMI was similar in normotensive and hypertensive subjects (-2.0 ± 1.6 and -2.3 ± 1.5, p = 0.246). However, DBP and SBP decreased significantly (-5.2 ± 7.1 mmHg, and -6.2 ± 12.5 mmHg, respectively, p < 0.001 for both) in hypertensive subjects, and increased in normotensive subjects (1.8 ± 9.3 mmHg, p = 0.041 and 2.7 ± 11.7 mmHg, p = 0.017, respectively). After 18 months, in the weight maintenance phase, BMI slightly increased (0.9 ± 1.3 kg/m2, p < 0.001) but remained significantly lower than at baseline (p < 0.0001). Unlike BMI, DBP and SBP increased significantly in hypertensive subjects (p < 0.001) and returned almost to baseline levels. Conclusions: Weight-loss intervention reduced BP in hypertensive patients, but this was not maintained in the long run.